New grid synchronization and power control scheme of doubly-fed induction generator based wind turbine system using fuzzy logic control. (June 2020) - Dida, Abdelhak; Merahi, Farid; Mekhilef, Saad
Highlights: Wind energy conversion system based on doubly fed induction generator is modeled. Start-up procedure and supervision of different operating stages is designed. Modified DPC scheme is designed to control rotational speed and reactive power. Modified DVC scheme is designed to control stator voltage amplitude and angle. PI-like Fuzzy controller is used to improve the system performance and robustness. Abstract: This paper deals with the analysis, modeling and control of a doubly-fed induction generator in variable speed wind turbine systems. The start-up procedure of the wind turbine including the grid synchronization has been established. New sensorless control schemes were developed, the first one is designed for standalone mode and grid synchronization named direct voltage control, the second one is designed for grid-connected mode named direct power control. To improve the robustness of the controlled system performance in case of machine parameters variations, a fuzzy logic controller was introduced. Various operation modes have been tested including accelerating and braking of the wind turbine, limited power and speed operation mode, power maximization mode, standalone operation mode with supplying a variable load. Simulation of the full start-up procedure was performed using Matlab/SimPowerSystems . The simulation results for several transient conditions demonstrated the effectiveness of the proposed control strategy. Graphical abstract: Reinforcing the robustness of the control system in wind turbine system by using a PI-like fuzzy logic controller. Image, graphical abstract